KEANEKARAGAMAN TUMBUHAN BERMANFAAT DI PEKARANGAN OLEH ETNIS SUNDA DI DESA SINDANG JAYA, KABUPATEN CIANJUR, JAWA BARAT - Silalahi, Marina (Universitas Tanjungpura, 2019)
AbstractThe Sundanese have been long used the home garden as a source of food, medicines, and construction materials. This study aims to document the plants diversity and its utilization in the Sindang Jaya Village, Disstict Cianjur, West Java. The research method was conducted by ethnobotany approach through surveys and interview. The data obtained were analyzed qualitatively by using descriptive statistics. This study foundÂ 100 species of the useful plants belonging 88 genera and 46 families in the yard in the Sindang Jaya home garden. The plants in the home garden uses as an ornamental (46 species), fruit (18 species), vegetable (14 species), and traditional medicine (species). The mangkokan (Polyschias scutellaria) and kedondong pagar (Polyscias fruticosa) are potential to be developed as the living fence as well as function as a source of food or vegetables. The Dioscorea hispida in home garden is one of the efforts of local communities to conserve wild plants.Keywords: Disocorea hispida, Etnis Sunda, Polyschias scutellaria, Polyscias fruticosa.